From Environmental Context to Digital Learning: Developing and Evaluating an Environment-Based Practicum E-Module for Green Chemistry - Siti Aisyah; Fitriani; Rizmahardian Ashari Kurniawan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop an Environment-Based Practicum E-Module for green chemistry and to evaluate its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the three-dimensional (3-D) development model, which consists of the Define, Design, and Develop stages. The participants were 28 tenth-grade students from Class X-A at SMAS Mujahidin Pontianak. Data were collected through interviews, classroom observations, expert validation sheets, student response questionnaires, and pretest–posttest assessments. The effectiveness evaluation in the Develop stage employed a one-group pretest–posttest design, with students completing a pretest before using the e-module and a posttest after the learning intervention. The data were analyzed using percentage analysis to determine the validity and practicality of the e-module, while its effectiveness was evaluated using the Normalized Gain (N-Gain) index. The results indicated that the developed e-module achieved average validity scores of 96% from material experts, 98% from media experts, and 98% from language experts, all of which were classified as highly valid. The practicality evaluation yielded an average score of 84%, indicating that the E-Module was highly practical. In addition, the effectiveness test produced an average N-Gain score of 0.86, which falls within the high category, as reflected by the increase in students’ mean scores from 85 on the pretest to 98 on the posttest. These findings demonstrate that the Environment-Based Practicum E-Module is valid, practical, and effective, making it a suitable digital instructional resource for supporting green chemistry learning, particularly in schools with limited laboratory facilities.